The Problem-Solving Process Utilizing Drifting in Akina in the Anime Series Initial-D - Alfian Irfa Darajat; Andy Bangkit Setiawan (LITERACY : International Scientific Journals of Social, Education, Humanities, 2023)
This research explores the process of adolescent problem resolution in Japan, specifically examining how drifting is employed as a means of conflict resolution among individuals within the context of the anime series titled "Initial D." The primary objective of this study is to gain insights into the process of problem resolution among adolescents through the utilization of drifting techniques. Adopting a qualitative research design with a thematic analysis approach, the researcher analyzes data extracted from episodes 1 to 5 of the anime "Initial D." The data collection entails transcribing dialogues that depict adolescents engaging in drifting races in Akina, competing against the tofu delivery driver, Takumi, a young man honing his skills to become the fastest racer in Akina, Japan. The findings from the investigation indicate that drifting emerges as a viable option for individual problem-solving among adolescents. This research also sheds light on the process of problem resolution adopted by both parties when seeking to resolve their conflicts through drifting. In conclusion, drifting serves as a medium for adolescent problem resolution in "Initial D," driven by the aspiration to surpass the fastest racer in Akina.Top of Form